What are the characteristics of people who use nicotine pouches and what types of pouches are being used? Data from an online cross-sectional survey of UK adults - Katherine East; Harry Tattan-Birch; Eve Taylor (PLoS ONE, 2025)
Introduction Use of nicotine pouches is rising but little independent data exist on the types of pouches used by UK adults. This study therefore assesses: (1) demographic characteristics associated with using nicotine pouches; (2) nicotine content, flavours, brands, and frequency of use of nicotine pouches. Methods Online cross-sectional Qualtrics survey of N = 2,967 UK adults (≥18 years) conducted May/June 2024. The sample were drawn from Prolific Academic using quotas (age, biological sex, ethnicity). Measures included demographics, vaping status, smoking status, frequency of nicotine pouch use, and pouch brand, flavour, and nicotine content used most often. Results Overall, 2.9% (n = 85) currently used, and an additional 10.1% (n = 299) had tried, pouches. Ever use declined with age and was most common among males (AOR = 1.80, 95%CI = 1.40–3.31) and those who currently vaped (AOR = 7.19, 4.80–10.75) or smoked (AOR = 5.80, 3.82–8.80). Nicotine pouch use was rare among adults who never smoked (3.0%) or never vaped (2.7%). Among adults who had ever used nicotine pouches (n = 384), half used Nordic Spirit (49.7%), most used mint/menthol flavours (60.7%), the most popular nicotine content was 11–20 mg (34.6%) although many did not know the nicotine content (28.4%), and around a fifth (19.5%) reported using them every day, with an additional fifth (21.9%) a few times a week, and a quarter tried once or twice (25.5%). Conclusions Among UK adults, nicotine pouches were predominantly used by those who currently/formerly smoke or vape and were also most popular among males and younger adults. Mint/menthol and 11–20 mg pouches were most popular and use frequency patterns varied substantially.